Reducing Opioid Prescriptions Through Patient Education and Standardized Protocols [14H]. (May 2020) - DePaula-Cox, Rose; Nair, Pallavi; Provost, Holly
Abstract : INTRODUCTION: Deaths due to opioid overdose continue to rise in the US. Initial exposure to opioids is largely due to surgical procedures. Our project hopes to reduce opioid needs and prescriptions after an outpatient laparoscopic procedure with a multi-disciplinary bundle pain management provided preoperatively. METHODS: Thirty narcotic-naïve patients undergoing laparoscopy underwent education of pain expectations, diet, bowel hygiene and exercise, and our 3 day treatment plan. Instruction was given at preoperative visit, anesthesia visit, day of procedure, and discharge. Patient inquiries about pain were made PODs #1 and after #4. Requests for opioid refills were monitored. Preop use of acetaminophen 1000 mg and gabapentin 1200 mg orally and lidocaine injected at trocar sites. Ketorolac 30 mg IV given at the end of the case. Only 6 oxycodone 5 mg tablets were prescribed for PRN needs. Three days of scheduled medication (acetaminophen, naproxen) given at discharge. IRB approval was waived. RESULTS: Three patients requested opioids but none were prescribed with pain management education. Six cases had endometriosis with only 2 of those patients requesting more opioids. The third patient had significant lysis of adhesions. CONCLUSION: This study emphasized the importance of repetitive pain management expectation discussions with patients. It also showed that having a more extensive surgery or source of preoperative pain does not require additional narcotics. 2/3 of patients with endometriosis did not request additional narcotics. This project will be expanded to all procedures while creating a standardized regimen for opioids and non-opioids postoperatively.